2019
DOI: 10.5194/isprs-annals-iv-3-w1-17-2019
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Fertilizer Usage Drives Agriculture Growth but Depletes Water Quality

Abstract: By 2050 most parts of India will be water stressed zones as most of the water resources are under heavy stress due to increasing nutrient contamination in their waters. In this scenario, studying the changes occurring in the freshwater nutrient contamination levels over a temporal scale is extremely important. This study focuses on monitoring the changes occurring in the nutrient contamination levels over a decade in a large reservoir known as Nagarjuna Sagar (NS) using remote sensing data. In this study, Land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Studies have shown that growing soybean production over time is accompanied by, in part, an increasing use of fertilizers (Tilman et al, 2001;FAO, 2018). In this sense, FAO (2019) estimates an average annual increase of 1.3% in world synthetic fertilizer demand for nitrogen (N), P, and K, and studies have shown that increases in fertilizer use can result in increased amounts of nutrients and toxins levels in ground and surface waters, incurring health and water purification costs and decreasing fishery and recreational values (Tilman et al, 2002;Kondraju and Rajan, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that growing soybean production over time is accompanied by, in part, an increasing use of fertilizers (Tilman et al, 2001;FAO, 2018). In this sense, FAO (2019) estimates an average annual increase of 1.3% in world synthetic fertilizer demand for nitrogen (N), P, and K, and studies have shown that increases in fertilizer use can result in increased amounts of nutrients and toxins levels in ground and surface waters, incurring health and water purification costs and decreasing fishery and recreational values (Tilman et al, 2002;Kondraju and Rajan, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This filtration is due to the low assimilation of fertilizers by plants, which only captures a small part of the fertilizers incorporated in the soil. In addition, this low assimilation generates that more quantity of fertilizers must be incorporated into the soil during the crop growth, which results in a higher production cost [7].…”
Section: Introductionmentioning
confidence: 99%
“…The conventional use of fertilizers usually leads to an excess of nutrients, due to their low assimilation by the plants. This fact makes this method ineffective, since a large quantity of fertilizer is necessary to perceive an improvement in the soil (Kondraju and Rajan, 2019). For this reason, it is necessary to find an alternative that helps introducing nutrients into plants and improves the assimilation efficiency of the conventional method.…”
Section: Introductionmentioning
confidence: 99%